Continuous Spectrum for a Class of Smooth Mixing CMV Matrices (Communications in Mathematical Research, 2025)
This note proves that the extended CMV matrices with Verblunskycoefficient that is generated by a smooth volume preserving mixing dynamicalsystem and a Hölder sampling function have almost surely continuous spectrum.